Pharmacologic inhibition by spironolactone attenuates experimental abdominal aortic aneurysms - Ladd, Zachary; Su, Gang; Hartman, Joseph; Lu, Guanyi; Hensley, Sara; Upchurch, Gilbert R.; Sharma, Ashish K. (Frontiers in Cardiovascular Medicine, 2023)
Background Abdominal aortic aneurysms (AAA) are characterized by vascular inflammation and remodeling that can lead to aortic rupture resulting in significant mortality. Pannexin-1 channels on endothelial cells (ECs) can modulate ATP secretion to regulate the pathogenesis of AAA formation. Our hypothesis focused on potential of spironolactone to inhibit EC-mediated ATP release for the mitigation of AAA formation. Methods A topical elastase AAA model was used initially in C57BL/6 (wild-type; WT) male mice. Mice were administered either a vehicle control (saline) or spironolactone and analyzed on day 14. In a second chronic AAA model, mice were subjected to elastase and β-aminopropionitrile (BAPN) treatment with/without administration of spironolactone to pre-formed aneurysms starting on day 14 and analyzed on day 28. Aortic diameter was evaluated by video micrometry and aortic tissue was analyzed for cytokine expression and histology. ATP measurement and matrix metalloproteinase (MMP2) activity was evaluated in aortic tissue on days 14 or -28. In vitro studies were performed to evaluate the crosstalk between aortic ECs with macrophages or smooth muscle cells. Results In the elastase AAA model, spironolactone treatment displayed a significant decrease in aortic diameter compared to elastase-treated controls on day 14. A significant increase in smooth muscle α-actin expression as well as decrease in elastic fiber disruption and immune cell (macrophages and neutrophils) infiltration was observed in mice treated with spironolactone compared to saline-treated controls. Spironolactone treatment also significantly mitigated pro-inflammatory cytokine expression, MMP2 activity and ATP content in aortic tissue compared to controls. Moreover, in the chronic AAA model, spironolactone treatment of pre-formed aneurysms significantly attenuated vascular inflammation and remodeling to attenuate the progression of AAAs compared to controls. Mechanistically, in vitro data demonstrated that spironolactone treatment attenuates extracellular ATP release from endothelial cells to mitigate macrophage activation (IL-1β and HMGB1 expression) and smooth muscle cell-dependent vascular remodeling (MMP2 activity). Conclusion These results demonstrate that spironolactone can mitigate aortic inflammation and remodeling to attenuate AAA formation as well as decrease growth of pre-formed aneurysms via inhibition of EC-dependent ATP release. Therefore, this study implicates a therapeutic application of spironolactone in the treatment of AAAs.